OP0240 Higher Expression of TNFR1 and IL-1R2 on Cell Surface of B*2705 Ankylosing Spondylitis Patients Vs B*2705 and B*2709 Healthy Subjects. Influence of Erap1 Polymorphism. (23rd January 2014) - Cauli, A.; Dessole, G.; Porru, G.; Cassotta, A.; Piga, M.; Vacca, A.; Ibba, V.; Garau, P.; Fiorillo, M. T.; Sorrentino, R.; Mathieu, A.
Abstract : Background: Ankylosing Spondylitis (AS) is a complex chronic inflammatory disease strongly associated with the majority of HLA-B27 alleles, with the exception of B*2706 and B*2709. GWAS studies have revealed that other genes are also involved in AS pathogenesis such as ERAP1 which is able to cleave TNFR1 and IL-1R2 cell surface receptors, supposed to play a pivotal role in AS pathogenesis. Objectives: To analyze the cell surface expression of TNFR1 and IL-1R2 receptors and the possible influence of ERAP1 allelic variance. Methods: The percentage of CD14 negative peripheral blood mononuclear cells (PBMC) expressing TNFR1 and IL-1R2 receptors on the cell surface was evaluated in 12 HLA-B*2705 patients with AS, 12 HLA-B*2705 healthy subjects (HC) and 12 HLA-B*2709 HC by means of flow cytometry analysis and CD120a and CD121b monoclonal antibodies, respectively. Patients and controls were genotyped for two ERAP1 SNPs associated with AS (rs27044 C/G and rs30187 C/T). Values were expressed as median percentage of positive cells (interquartile range). The differences between AS patients and HC were analyzed by Mann Whitney U-test. Results: TNFR1 expression on PBMC was significantly higher in AS patients (35.5 IQR 15.9-60.4) compared to B*2705 HC (18.9 IQR 9.7-25.5, p=0.04) and B*2709 HC (13.1 IQR 9.3-21.5, p=0.02). IL-1R2 was also significantly higher in AS patients (1.5 IQR 0.6-2.5) compared to B*2705 HC (0.2 IQR 0.1-0.8, p=0.01) and B*2709 HC (0.6 IQR 0.1-1.6, p=ns). The majority of AS patients and HC were heterozygous both for rs27044 (C/G) and rs30187 (C/T); the higher numbers of TNFR1 and IL-1R2 positive cells found in AS patients compared to HC were not due to differences in the ERAP1 allelic distribution in patients and controls as shown in the figure below: Image/graph: Conclusions: This study shows a higher expression of TNFR1 and IL-1R2 on the PBMC surface of AS patients compared to B*2705 and B*2709 regardless of ERAP1 allelic variance, underlining the important role of these two cytokines in the pathogenesis of AS. Disclosure of Interest: None Declared